Faire jardiner la rue pour en faire un jardin ? Le projet de la rue Kléber à Bordeaux à l’épreuve des pratiques et des représentations habitantes (2011-2016) - Aurélien Ramos (Développement Durable et Territoires)
Drawing on a project of a garden-street designed and implemented by the City of Bordeaux in 2011, this article focuses on how garden is used by the municipality as a tool to modify the way how citizens use and see urban public spaces. Through the analysis of the interactions forms between the citizens and their street, the gardeners-citizens and the cultivated plants and between the citizens themselves, we show the gap between the municipality’s ambitions and the way how the citizens grasp the requalification of the street as garden-street. However, the plants introduced in the street transformed the social interactions between the citizens, the garden-street project fails to create a collective dynamic on gardening in the street. It allows nevertheless the coexistence of individual gardening practices which contribute scatteringly to an urban landscape production.